A comparison of laboratory-based kayak testing protocols - Jones, M. J.; Peeling, P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To compare the differences in peak oxygen uptake (VO2peak) and lactate threshold (LT2) between the 7 × 4-min incremental step test (7-ST) and the maximal accumulated oxygen deficit (MAOD) test protocols in sprint kayak athletes. Methods: Nine highly trained kayak athletes performed the 2 laboratory test protocols. The 7-ST involved six 4-min submaximal incremental stages, each separated by a 1-min recovery, before a 4-min all-out effort. The MAOD test involved four 4-min submaximal incremental stages (also with each stage separated by a 1-min recovery), followed by 20-min recovery and a 4-min all-out effort. Results: No statistically significant differences in VO2peak were recorded between the 2 protocols (P > .05). However, distance covered, power output, stroke rate, and speed were almost certainly greater in the MAOD test (magnitude-based inference: 99-100% positive), while blood lactate (BLa), heart rate (HR), and rating of perceived exertion (RPE) were likely lower (magnitude-based inference: 78-92% negative). The derived measures of LT2 (excluding HR) were not different between the 2 protocols. Conclusion: The results of this study suggest that both the 7-ST and MAOD test protocols are comparable with regard to the measurement of VO2peak and LT2 in highly trained sprint kayak athletes. However, since differences in the measures of distance traveled, power, stroke rate, HR, BLa, and RPE were reported in the maximal stage of the these 2 test protocols, their interchangeable use in a laboratory setting is not ideal if the data output is to be compared and contrasted over time.